Clinical Predictors of Children with Bronchial Asthma admitted to the Intensive Care Unit at Tripoli Children’s Hospital - Fadelah Elghadban; Azza Kara; Hajer Abutrouma (AlQalam Journal of Medical and Applied Sciences, 2023)
The severity of acute asthma is determined based on symptoms and signs such as respiratory rate (RR), wheezing, retractions, and oxygen saturation (OS). The main aim of the study is to compare the demographic and clinical characteristics of bronchial asthma among children admitted to the general ward with those among children admitted to the PICU. A cross sectional and analytical study, 100 patients with bronchial asthma were enrolled from January 2016 to January 2019 (70 admitted in the paediatric ward and 30 in Paediatric Intensive Care Unit). The data was collected by filling in the data by reviewing patient files and data included initial Heart Rate (HR), Respiratory Rate (RR). Oxygen Saturation in Arterial Blood (SaO2) and Partial Pressure of Carbon Dioxide in Arterial Blood (PaCo2). Male children were more commonly recorded than female children, and there is no significant gender dominancy between the two groups (P = 0.965). Our data also indicate that there is not a significant age difference between the children in the PICU and general ward groups (P = 0.543). There were significant differences in two groups (Ward admitted and PICU admitted) with respect to initial heart rate (P = 0.02), respiratory rate (P = 0.03), arterial oxygen saturation (P = 0.02), PaCO2 (P = 0.03). There was a significant correlation between initial vital sign, blood gas analysis. It indicates usefulness of these factors as predictors of severe asthma attack. Age and gender were not risk factors for severe attack in our study. يتم تحديد شدة الربو الحاد بناءً على الأعراض والعلامات مثل معدل التنفس والصفير والانقباضات وتشبع الأكسجين. الهدف الرئيسي من الدراسة هو مقارنة الخصائص الديموغرافية والسريرية للربو القصبي بين الأطفال الذين تم إدخالهم إلى الجناح العام مع تلك الموجودة بين الأطفال الذين تم إدخالهم إلى وحدة العناية المركزة للأطفال. في دراسة مقطعية وتحليلية، تم تسجيل 100 مريض مصاب بالربو القصبي من يناير 2016 إلى يناير 2019 (70 تم إدخالهم إلى جناح الأطفال و30 في وحدة العناية المركزة للأطفال). تم جمع البيانات عن طريق ملء البيانات من خلال مراجعة ملفات المرضى وتضمنت البيانات معدل ضربات القلب الأولي ومعدل التنفس. تشبع الأكسجين في الدم الشرياني والضغط الجزئي لثاني أكسيد الكربون في الدم الشرياني. كان تسجيل الأطفال الذكور أكثر شيوعًا من الأطفال الإناث، ولا توجد هيمنة جنسية كبيرة بين المجموعتين (P = 0.965). تشير بياناتنا أيضًا إلى عدم وجود فرق كبير في العمر بين الأطفال في وحدة العناية المركزة لحديثي الولادة ومجموعات الجناح العامة (P = 0.543). كانت هناك اختلافات كبيرة في المجموعتين (الجناح ووحدة العناية المركزة لحديثي الولادة) فيما يتعلق بمعدل ضربات القلب الأولي (P = 0.02)، ومعدل التنفس (P = 0.03)، وتشبع الأكسجين الشرياني (P = 0.02)، وضغط ثاني أكسيد الكربون (P = 0.03). كان هناك ارتباط كبير بين العلامة الحيوية الأولية وتحليل غازات الدم. يشير إلى فائدة هذه العوامل كمؤشرات لنوبة الربو الشديدة. لم يكن العمر والجنس عوامل خطر للنوبة الشديدة في دراستنا